Volume 2: Fuel Cycle and High Level Waste Management; Computational Fluid Dynamics, Neutronics Methods and Coupled Codes; Stude 2008
DOI: 10.1115/icone16-48210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Analysis of Prediction Methods for Two-Phase Flow Pressure Drop in Mini-Channels

Abstract: 2092 data of two-phase flow pressure drop were collected from 18 published papers of which the working fluids include R123, R134a, R22, R236ea, R245fa, R404a, R407C, R410a, R507, CO2, water and air. The hydraulic diameter ranges from 0.506 to 12mm; Relo from 10 to 37000, and Rego from 3 to 4×105. 11 correlations and models for calculating the two-phase frictional pressure drop were evaluated based upon these data. The results show that the accuracy of the Lockhart-Martinelli method, Mishima and Hibiki correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
1
37
2
Order By: Relevance
“…Based on the separated flow model, studies of Sun and Mishima [13] and Wang et al [14] indicated that the index value n of Martinelli parameter X in Chisholm correlation [15] is not 1, as shown in Eq. (11).…”
Section: Frictional Resistance Correlation Under Steady Conditionmentioning
confidence: 98%
“…Based on the separated flow model, studies of Sun and Mishima [13] and Wang et al [14] indicated that the index value n of Martinelli parameter X in Chisholm correlation [15] is not 1, as shown in Eq. (11).…”
Section: Frictional Resistance Correlation Under Steady Conditionmentioning
confidence: 98%
“…A C C E P T E D ACCEPTED MANUSCRIPT 7 Lee and Garimella [8] paid a great attention on the channel size effect, and applied regression analysis to obtain a new correlation of pressure drop for saturated boiling of water. Phan et al [9] observed that the total two-phase pressure drop of water significantly increases with static contact angle.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Sun and Mishima [7] collected 2092 data from 18 published papers using 12 kinds of working fluids, evaluated 11 correlations and models for calculating the two-phase frictional pressure drop, and also proposed a modified…”
Section: Introductionmentioning
confidence: 99%
“…A very large databank for pressure drop has been built in the literature. Apart from experiments, various forms of two-phase multiplier have been proposed to predict the pressure loss, as summarized by Sun and Mishima (2009). In this method, the pressure drop correlation of single phase flow is required to be provided first, and many of them are semi-experimental based.…”
Section: Pressure Gradientmentioning
confidence: 99%
“…Many researchers have investigated the pressure gradient of annular flow in different diameter tubes through experimental methods, such as Cioncolini et al (2009), Shannak (2008, and Sun and Mishima (2009). A very large databank for pressure drop has been built in the literature.…”
Section: Pressure Gradientmentioning
confidence: 99%